Analisis Tentang Mekanika Kuantum Dan Hubunganya Dengan Teori Medan - Humendru, Dwi Cantika; Zebua, Elnatan (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
This literature analysis examines the interrelationship between quantum mechanics and quantum field theory, two foundational frameworks in modern physics. Quantum mechanics, developed in the early 20th century, revolutionized our understanding of subatomic particles through principles of probability and uncertainty. Meanwhile, quantum field theory integrates these quantum concepts with relativistic principles, providing a comprehensive framework for understanding particle interactions and fundamental forces. This study aims to explore the historical development, key concepts, and ongoing challenges in merging these two theories. By synthesizing existing literature, we aim to illuminate the complexities and significance of their interplay, offering insights that may benefit researchers and students alike in the field of theoretical physics.